Evaluation of the food service for adolescent boys in Mogale Child and Youth Care Centre in Gauteng, South Africa, 2012 - Rendall-Mkosi, Kirstie Margaret (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2014.